Geosynthetic strain gage installation procedures and alternative strain measurement methods for roadway applications. Issue 6 (December 2010) - Warren, K.A.; Christopher, B.; Howard, I.L.
Abstract : ABSTRACT: The measurement of geosynthetic strain is important to the development of numerical models that can predict the behavior of geosynthetic-reinforced flexible pavements. This paper outlines the key issues regarding foil strain gage selection, installation, and calibration on geosynthetics for dynamic strain measurement in roadway applications. The flexible nature of geosynthetics and the interaction of these materials with the adjacent layers of the pavement structure in a dynamic loading application limit the ability to use all types of strain gages and adhesives. While this paper does not cover every type of geosynthetic, it provides sufficient procedural details and illustrations of foil strain gage installations on a variety of geosynthetics (woven geotextiles and geogrids, nonwoven geotextiles and punch/drawn geogrids) and then outlines several alternative methods (wire extensometers, inductance coils and fiber optics) of dynamic strain measurement. While foil strain gages and closely spaced wire extensometers provide a localized value of displacement on a geosynthetic, wire extensometers and inductance coils provide a measure of global displacement (which includes slack in the geosynthetic) and redundancy in total strain measurements. Fiber optics is an emerging and very promising method of accurately measuring strain in geosynthetics, and at least one delivery system has been developed.